COX-2 inhibitors: a potential target for drug therapy in the management of colorectal cancer - Ryan, A R; Rosita, A R; Khalid, Kamarul Ariffin; Qureshi, Akhtar (Malaysian Medical Association, 1999)
Colorectal cancer is currently the third most common cancer in Malaysia. Elevated expression of COX-2, an induced cyclooxygenase isoenzyme, has been seen in colonic adenomas and colorectal carcinoma. There is evidence that inhibition of this COX-2 can decrease the risk of colorectal cancer. Selective COX-2 inhibitors may have a role in reducing the risk of colorectal cancer in high-risk individuals.